2022
DOI: 10.56392/001c.56675
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Recovery from Delirium: An International Survey of Healthcare Professionals Involved in Delirium Care.

Abstract: Background A crucial part of delirium care is determining if the delirium episode has resolved. Yet, there is no clear evidence or consensus on which assessments clinicians should use to assess for delirium recovery. Objective To evaluate current opinions from delirium specialists on assessment of delirium recovery. Design Online questionnaire-based survey distributed internationally to healthcare professionals involved in delirium care. Methods The survey covered methods for assessing recovery, the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This is essential to communicate details of care to the patient and their relatives, to ensure fewer patient discharges with unresolved delirium and to inform treatment. A recent international survey of clinicians involved in delirium care found that the most used repeat assessments measured a range of delirium features used including level of arousal, inattention, motor disturbance and psychotic features 83 . Notably, delirium‐specific tools were reported to be used by clinicians rather than tests of general cognition such as the MMSE; this provides an interesting contrast to the research literature summarised in the present review.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This is essential to communicate details of care to the patient and their relatives, to ensure fewer patient discharges with unresolved delirium and to inform treatment. A recent international survey of clinicians involved in delirium care found that the most used repeat assessments measured a range of delirium features used including level of arousal, inattention, motor disturbance and psychotic features 83 . Notably, delirium‐specific tools were reported to be used by clinicians rather than tests of general cognition such as the MMSE; this provides an interesting contrast to the research literature summarised in the present review.…”
Section: Discussionmentioning
confidence: 68%
“…A recent international survey of clinicians involved in delirium care found that the most used repeat assessments measured a range of delirium features used including level of arousal, inattention, motor disturbance and psychotic features. 83 Notably, delirium-specific tools were reported to be used…”
Section: Implications For Research and Clinical Practicementioning
confidence: 99%